MEDIA SOSIAL SEBAGAI SUMBER PEMBELAJARAN INOVATIF PENDIDIKAN AGAMA ISLAM - Syafe'i, Syafe'i; Chanifudin, Chanifudin (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Univesitas Muhammadiyah Bengkulu, 2026)
The advancement of digital technology has propelled the use of social media as an innovative learning resource, including in Islamic Religious Education (PAI). This study aims to analyze the utilization of social media as a PAI learning source based on prior research findings. Employing a qualitative approach through journal review (literature review), data were sourced from reputable national and international scholarly articles on social media, learning innovation, and PAI. Data analysis utilized content analysis techniques to identify forms of utilization, contributions, and challenges of social media in PAI learning. Findings reveal that platforms like YouTube, Instagram, TikTok, WhatsApp, Telegram, and Facebook serve as supplementary learning resources that enhance access to materials, student motivation, and engagement. However, challenges persist, including inconsistent content quality and risks of unverified religious information. Thus, content curation, strengthened digital literacy, and pedagogical integration by teachers are essential to align social media use with PAI learning objectives under the Merdeka Curriculum